4-HNE Immunohistochemistry and Image Analysis for Detection of Lipid Peroxidation in Human Liver Samples Using Vitamin E Treatment in NAFLD as a Proof of Concept. (September 2020) - Podszun, Maren C.; Chung, Joon-Yong; Ylaya, Kris; Kleiner, David E.; Hewitt, Stephen M.; Rotman, Yaron
Lipid peroxidation is a common feature of liver diseases, especially non-alcoholic fatty liver disease (NAFLD). There are limited validated tools to study intra-hepatic lipid peroxidation, especially for small specimen. We developed a semi-quantitative, fully automated immunohistochemistry assay for the detection of 4-hydroxynoneal (4-HNE) protein adducts, a marker of lipid peroxidation, for adaptation to clinical diagnostics and research. We used Hep G2 cells treated with 4-HNE to validate specificity, sensitivity, and dynamic range of the antibody. Staining and semi-quantitative automated readout were confirmed in human needle-biopsy liver samples from subjects with NAFLD and normal liver histology. The ability to detect changes in lipid peroxidation was tested in paired liver biopsies from NAFLD subjects, obtained before and after 4 weeks of treatment with the antioxidant vitamin E (ClinicalTrials.gov NCT01792115, n =21). The cellular calibrator was linear and NAFLD patients had significantly higher levels of 4-HNE adducts compared to controls ( p =0.02). Vitamin E treatment significantly decreased 4-HNE ( p =0.0002). Our findings demonstrate that 4-HNE quantification by immunohistochemistry and automated image analysis is feasible and able to detect changes in hepatic lipid peroxidation in clinical trials. This method can be applied to archival and fresh samples and should be considered for use in assessing NAFLD histology.